OVERVIEW OF BACTERIA TYPES AND ANTIBACTERIAL RESISTANCE PATTERNS AMONG PATIENTS WITH URINARY TRACT INFECTIONS - MAHMUDA, IIN N. N.; AFFIFAH, FATHIYYA N.; AGUSTINA, TRI; PRASETYO, ANDRI S.; KANIA, YULIA I.; FAIZAH, ISHMAH N. (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to characterize bacterial types and antibacterial resistance patterns in UTI patients in Surakarta. Methods: The study was conducted at PKU Muhammadiyah Surakarta Hospital using a descriptive observational design of demographic data and bacterial culture results that were tested for antibiotic resistance with a cross-sectional approach. A total of 56 UTI patients were included through total sampling of inpatients at PKU Muhammadiyah Surakarta Hospital. Patient demographic data were collected from medical records and antibiotic sensitivity test results were performed on urine bacterial culture results with bactec media using a VITEK 2 compact culture machine. Results: Of the 56 patients, 43 were infected with Gram-negative bacteria and 13 with Gram-positive bacteria. Fourteen bacterial species were identified, with non-ESBL Escherichia coli being the most prevalent (33.9%), followed by Klebsiella pneumoniae (10.7%), ESBL strain E. coli (8.9%), Staphylococcus aureus (8.9%), Enterobacter cloacae (8.9%), Streptococcus sp. (7.1%), Pseudomonas aeruginosa (5.4%), and Enterococcus faecalis (5.4%). The remaining species, each representing 1.8% of the cases, included Flavimonas oryzihabitans, Kluyvera sp., Raoultella ornitholytica, Proteus mirabilis, Aeromonas hydrophila, and Staphylococcus epidermidis. Conclusion: This study revealed diverse resistance patterns among different g-positive and g-negative bacterial species against the tested antibiotics based on local bacterial patterns. These findings emphasize the importance of ongoing surveillance and targeted antibiotic strategies in effectively managing UTIs with local antibiotic stewardship management.